Examining the Interplay Between Big Data and Microservices – A Bibliometric Review - Daniel Staegemann; Matthias Volk; Aamir Shakir; Erik Lautenschläger; Klaus Turowski (Complex Systems Informatics and Modeling Quarterly)
Due to the ever increasing amount of data that is produced and captured in today’s world, the concept of big data has risen to prominence. However, implementing the respective applications is still a challenging task. This holds especially true, since a high degree of flexibility is desirable. One potential approach is the utilization of novel decentralized technologies, as in the case of microservices to construct such big data analytics solutions. To obtain an overview of the current situation regarding the corresponding research, using the scientific database Scopus and its provided tools for search and analytics, this bibliometric review provides an analysis of the literature and subsequently discusses avenues for future research.